The Effect of Location and Tourism Facilities on Tourist Satisfaction in Bongo Village, Batudaa Pantai District, Gorontalo Regency: Pengaruh Lokasi Dan Sarana Wisata Terhadap Kepuasan Wisatawan Di Desa Bongo Kecamatan Batudaa Pantai Kabupaten Gorontalo - Nurhasmi Hasmi; Dian Dwinasary Ridwan; Fitriani Fitriani; Ariawan Ariawan (Journal of Technopreneurship on Economics and Business Review, 2023)
Pantai District, Gorontalo Regency. In Bongo Village there are tours that have their own charm, the beauty of the beach or natural panorama that can become a leading tourist attraction. The research objective was to determine the effect of location and tourism facilities on tourist satisfaction in Bongo Village, Batudaa Pantai District, Gorontalo Regency. The population in this study was the number of visitors in June 2008 as many as 1,183 people who were in Bongo Village, Batudaa Pantai District, Gorontalo Regency. The research method used is a survey research method used to explain casual relationships and hypothesis testing. Tests were carried out with the path analysis test (Path Analisys). The results showed that location and tourist facilities simultaneously and partially had a positive and significant effect on tourist satisfaction in Bongo Village, Batudaa Pantai District, Gorontalo Regency.